Penerapan Model Pembelajaran Learning Cycle (LC) Tipe 5 E dalam Peningkatan Hasil Belajar Fisika Materi Induksi Elektromagnetik Kelas XII-IPA-1 SMA Negeri 1 Sukamulia - Bahry, Saiful (Lembaga Yasin AlSys, 2023)
Physics is one of the exact subjects contained in the curriculum, which is the basis for technological developments. This is evidenced by the many technological products developed using the concept of physics. Even in the current KTSP (Education Unit Level Up Curriculum), Physics is one of the subjects that is tested nationally. But in reality at this time there is still an assumption that students think that physics is a difficult subject, this is due to physics as well as consisting of concepts and Latin terms which are difficult for students to understand. This causes students' interest in learning to decrease, thus affecting learning outcomes. The purpose of conducting this class action research (PTK) is to find out the Type 5 E Learning Cycle (LC) Learning Model in improving student achievement in Physics lessons. This action research was conducted in 3 cycles. From the results of the actions taken it is proven to be able to improve student achievement by achieving ideal standards. From 55.57% to 72.88%, and 88.07, classically it has achieved completeness. The results of this action research indicate that the application of the Type 5 E Learning Cycle (LC) Learning Model can improve student learning outcomes in class XII-IPA-1 with completeness reaching 100%, thus the application of the demonstration method is effective in increasing student achievement in Physics lessons at Public Senior High Schools 1 Sukamulia, Kab. East Lombok.